How to grasp the public? Governmental communication in the Netherlands - van Wessel, Margit (Javnost-The Public, 2008)
The Dutch government, like many other governments of advanced democracies, finds itself confronted with political disaff ection. Recent cabinets have searched for ways to reconnect with citizens. The main argument made in the article is that these eff orts are saddled with constructions of the public, which pre-empt the transformation of citizen-government relations that the government seeks. The article shows that there are many instances in which we find that government’s theories and practices of communication for reconnection are rooted in constructions of the public as a present and clearly defi ned entity, as ready and eager for constructive interaction, and for interaction about specific policies. It is argued that both assumptions about citizens fi tting these constructions and attempts at connection through these constructions are problematic. Finally, the article discusses possibilities for alternative constructions of the public, which suggests that the connection is possible if the public is constructed diff erently.